Impact of Retention and Development on Turnover Intention among Gen Z at Bank BNI - Revina Armayani; Imas Soemaryani (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Generation Z, a growing segment of Indonesia’s workforce, shows high turnover intentions, creating retention challenges for organizations. At PT Bank Negara Indonesia (BNI) Regional Office 04, more than 60% of recent resignations involved this demographic. This study aims to investigate the effect of employee retention and employee development on turnover intention among Generation Z employees. A quantitative research design was applied using a survey of 132 respondents selected through purposive sampling. Data were analyzed using path analysis with SPSS to assess individual and joint effects. Results show that employee retention significantly reduces turnover intention by 57.1%, largely driven by strong employee relations and clear career advancement opportunities. Employee development also decreases turnover intention by 29.4%, though its impact is constrained by less effective training delivery. Combined, these variables explain 64.28% of the variance in turnover intention, indicating a substantial negative influence. The findings suggest that enhancing competitive rewards, career pathways, and interactive training can be effective strategies for reducing turnover intention and fostering loyalty among Generation Z employees in the banking sector.